Respuesta :
Answer: [tex]\bold{x^4+6x^3-12x-72}[/tex]
Step-by-step explanation:
[tex]f(x) = \sqrt{x^2+12x+36} \implies f(x)=\sqrt{(x+6)^2}\implies f(x) = x+6\\\\\\f(x)\cdot g(x)=(x+6)(x^3-12)\\.\qquad \qquad =x(x^3-12)+6(x^3-12)\\.\qquad \qquad =x^4-12x +6x^3-72\\.\qquad \qquad =\large\boxed{x^4+6x^3-12x-72}[/tex]
The expression equal to f(x)·g(x) is [tex]x^{4} + 6x^{3} - 12x - 72[/tex] .
What is the equivalent expression of f(x)·g(x) after simplification ?
The expressions given are f(x) = [tex]\sqrt{x^{2}+12x+36}[/tex] and g(x) = [tex]x^{3} - 12[/tex] .
Thus we have
⇒ f(X) = [tex]\sqrt{x^{2}+12x+36}[/tex]
⇒ f(x) = [tex]\sqrt{(x+6)^{2} }[/tex]
⇒ f(x) = x + 6 .
Therefore the expression of multiplication of f(x)·g(x) is =
= [tex](x^{3} - 12)*(x + 6)[/tex]
= [tex]x^{4} + 6x^{3} - 12x - 72[/tex]
Thus, the expression equal to f(x)·g(x) is [tex]x^{4} + 6x^{3} - 12x - 72[/tex] .
To learn more about simplification of expression, refer -
https://brainly.com/question/723406
#SPJ2